Potential global distribution area projections of the aphid Lipaphis erysimi and its predator Eupeodes corollae in the context of climate change - Lian, Yuyang; Wang, Aqiang; Peng, Sihua; Jia, Jingjing; Yang, Xiaofeng; Li, Jinlei; Yang, Shuyan; Zheng, Rongjiao; Zhou, Shihao (Frontiers in Plant Science, 2022)
Climate change affects the population distribution of pests and their natural enemies, and predicting these effects is necessary for pest monitoring and green control. Lipaphis erysimi is an important vegetable pest, and its natural enemy, the Eupeodes corollae Fabricius has a strong predatory effect on the L. erysimi. To assess the spread trends of L. erysimi and its natural enemy, the hoverfly, E. corollae under current (1970-2000) and future climates (2041-2060), based on the MaxEnt model, this paper uses data on the geographical distribution of the historical occurrence of L. erysimi and E. corollae to speculate on their potential distribution areas worldwide and analyze the key environmental factors affecting the survival and spread of both. The results showed that the Representative Concentration Pathway (RCP) 2.6 and RCP4.5 climatic conditions are favorable for the spread of L. erysimi, the RCP8.5 climatic conditions are unfavorable for the spread of L. erysimi, and all three future climatic conditions are unfavorable for the spread of E. corollae. The highest fitness of L. erysimi was found at the annual average temperature of 18 °C and the annual average precipitation of 900 mm, while the highest fitness of E. corollae was found at the annual average temperature of 10 °C and the lowest temperature in the coldest month of 0 °C. This study can provide a reference basis for monitoring and early warning and biological control of L. erysimi.